Current knowledge about early childhood caries in the gulf cooperation council with worldwide reflection: Scoping review of the scientific literature (2010–2021) - Asmaa Othman Alkhtib; Hasaan G. Mohamed (PLOS Global Public Health, 2023)
Early childhood caries (ECC) is one of the most prevalent chronic childhood diseases affecting the primary teeth of children younger than 6 years of age. The disease etiology is complex and includes social, biological, and dietary factors. This review aims to explore the knowledge of ECC prevalence globally and locally within the Gulf Cooperation Council (GCC) countries during the years 2010–2021. Another aim is to explore oral health promotion programs with more focus on the GCC region. A search was conducted in PubMed, Medline, Scopus, the Cochrane Collaboration database, and Google Scholar to identify relevant studies published between 2010 and 2021 using specific keywords. Studies that utilized both the World Health Organization criteria and International Caries Detection and Assessment System for dental caries assessment were included. The included studies indicated considerable variation in the reported prevalence of ECC. While developed countries show low prevalence, countries in the GCC and other Arab countries show a high prevalence of ECC. Many oral health promotion programs were identified globally including oral health education, nutritional programs, the use of fluoride and pit-and-fissure sealants, and inter-professional population-based oral health promotion and prevention programs such as school-based oral health programs, motivational interviewing, and anticipatory guidance. ECC remains a significant problem in many parts of the world including the GCC region. Oral health prevention programs have been established within the GCC region. Nevertheless, the GCC region has some unique characteristics that need to be investigated to contextualize the western model of the dynamics of ECC prevention and promotion programs locally.